Competence development as a means of HR management in the field of social work - Ježková Petrů, Gabriela; Zychová, Kristýna (Frontiers in Psychology, 2023)
Professional competences in social services are becoming the subject of interdisciplinary cooperation and require a multidisciplinary approach. The research aimed to identify which professional competences are required by social service managers, to determine which variables influence the expansion of social work competences and to categorize the professional competences. Expansion of social work competences is influenced by many factors according to specific characteristics of the organization. The results were obtained through a questionnaire survey of managers (n = 247) and employees (n = 219). All organizations providing social services in the Czech Republic, according to the Register of Social Service Providers of the Ministry of the Interior of the Czech Republic, were contacted. The results were used for formulating a competency model for social services. The relationship between the selected variables and the expansion of social work competences was tested using a dependency test (χ2). The significant level of value was chosen as α = 0.05. The strength of dependence was calculated using a Cramer’s V measurement within 0 ≤ V ≤ 1. The result of the measurement was to test the validity of the hypothesis (hypothesis testing), and the result of the test was related back to the theory (verification). Factor analysis enabled the relationships between the latent variables to be uncovered and allowed two groups to be formed within the professional competences. Results showed a relationship between the expansion of competences through continuing education, the evaluation of personal development and motivation plans, and the establishment of a set of professional competences for each job. The results suggest that achieving a particular competency should be part of a workforce development plan. Factor analysis revealed two groups of professional competences. The first group includes competences such as socio-legal counseling, analytical, methodological, and conceptual activities in the social field, and social counseling and social rehabilitation. The second group includes competences such as professional activities in facilities providing social prevention services, social diagnostics, and identifying the needs of the population and the region.